2019
DOI: 10.1007/s00227-019-3506-4
|View full text |Cite
|
Sign up to set email alerts
|

Host selection and ovipositor length in eight sympatric species of sculpins that deposit their eggs into tunicates or sponges

Abstract: Interspecific interactions between parasites and hosts can influence the evolution of behavioural and morphological adaptations of both parasites and their hosts. There is, however, little empirical evidence available regarding the evolution of reproductive traits driven by these interactions. In this paper, we investigated host selection and ovipositor length in nine sympatric marine sculpins that oviposit into tunicates or sponges. Field and genetic studies have revealed host use for eight out of nine specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…However, the process, procedure, and prior behaviors of reproduction (e.g., territoriality, intra-and intersexual selection, courtship, and spawning behavior), which are key to understanding the adaptive signi cance and evolutionary background of reproductive strategies in the deep-sea environment, have not been observed. From another point of view, it is expected that the dispersion of spawning substrate utilization makes the species with similar spawning niches less di cult to live sympatrically because it reduces interspeci c competition (Reichard et al 2007;Awata et al 2019). There is a possibility that the unique preference for the spawning substrate in snail shes has a similar function to the above.…”
Section: Introductionmentioning
confidence: 99%
“…However, the process, procedure, and prior behaviors of reproduction (e.g., territoriality, intra-and intersexual selection, courtship, and spawning behavior), which are key to understanding the adaptive signi cance and evolutionary background of reproductive strategies in the deep-sea environment, have not been observed. From another point of view, it is expected that the dispersion of spawning substrate utilization makes the species with similar spawning niches less di cult to live sympatrically because it reduces interspeci c competition (Reichard et al 2007;Awata et al 2019). There is a possibility that the unique preference for the spawning substrate in snail shes has a similar function to the above.…”
Section: Introductionmentioning
confidence: 99%
“…Among marine fishes, host invertebrates used by ostracophilous fishes are diverse. Blennies, marine sculpins, sea ravens, poachers and snailfishes oviposit in the spongocoels of sponges (Busby et al, 2012;Chernova, 2014;Karplus, 2014;Momota & Munehara, 2017) and in the branchial chambers of crabs (e.g., Gardner et al, 2016;Hunter, 1969;Matsuzaki et al, 2020;Poltev & Mukhametov, 2009), whereas the Japanese tubesnout Aulichthys japonicus Brevoort, 1862 (Akagawa et al, 2008) and marine sculpins (Awata et al, 2019;Goto & Oba, 2019;Nishida et al, 2008) oviposit in the atria of tunicates. As has been found in freshwater bitterlings, ostracophilous snailfishes and sculpins have elongated ovipositors (Awata et al, 2019;Hunter, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…The marine sculpins (Psychrolutidae, 64 genera, 214 species) and sea ravens and poachers (Agonidae, 25 genera 59 species), that belong to the Infraorder Cottales (Betancur-R et al, 2017;Nelson et al, 2016;Smith & Busby, 2014), represent a diverse group exhibiting morphological variation associated with specific reproductive strategies (Abe & Munehara, 2009;Buser et al, 2017;Knope, 2013;Koya et al, 2011). They represent an ideal system to study morphological and behavioural adaptations driven by the interactions between parasites and hosts because several sculpins, sea ravens and poachers are known to parasitize live invertebrates for egg deposition (Abe & Munehara, 2009;Busby et al, 2012;Karplus, 2014;Momota & Munehara, 2017), and a recent study has shown that ostracophilous marine sculpins exhibit interspecific variation in host selection and female reproductive traits such as ovipositor length (Awata et al, 2019). There are three patterns of host use by ovipositing sculpins including species that primarily use colonial tunicates, those that exclusively use solitary tunicates and those that use exclusively sponges (Awata et al, 2019), showing host specificity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations